Peran Mahasiswa Sebagai Agent of Change dalam Kehidupan Masyarakat - Fanny Khaerunnisa (Proceedings Series of Educational Studies, 2023)
Abstract: College students as intellectuals are considered to be capable and qualified figures so they can contribute to society. College students based on social concern with their critical thinking can create reforms that make students as agents of change. This study uses the library study method with a qualitative descriptive research type whose aim is to determine the role of students as agents of change in life in society.Keywords: College students, agent of changeAbstrak: Mahasiswa sebagai kaum intelektual dianggap menjadi sosok yang cakap dan berkualitas sehingga dapat berkontribusi untuk masyarakat. Mahasiswa berlandaskan kepedulian sosial dengan pemikiran kritisnya dapat menciptakan reformasi yang menjadikan mahasiswa sebagai agent of change. Penelitian ini menggunakan metode studi kepustakaan dengan jenis penelitian deskriptif kualitatif yang tujuannya untuk mengetahui peran mahasiswa sebagai agent of change dalam kehidupan di masyarakat.Kata kunci: Mahasiswa, agent of change